DATABASE OF GEOMAGNETIC OBSERVATIONS IN RUSSIAN ARCTIC AND ITS APPLICATION FOR ESTIMATES OF THE SPACE WEATHER IMPACT ON TECHNOLOGICAL SYSTEMS - O.V. Kozyreva; V.A. Pilipenko; M.N. Dobrovolsky; A.N. Zaitsev; E.E. Marshalko (Solar-Terrestrial Physics, 2022)
An archive of digital 1-min data from Soviet/Russian Arctic magnetic stations has been created, starting from 1983 to the present. The archive includes data from stations deployed along the Arctic coast by various USSR/Russia institutes. All data are divided into daily files, converted into a standard IAGA2002 format, and provided with graphs for quick-look browsing. Some of the data are not included in the existing world data portals (SuperMAG, INTERMAGNET). We give examples of using the database for the Arctic: study of irregular disturbances and waves of the Pc5/Pi3 range exciting intense geomagnetically induced currents; distortion of the pipe-to-soil potential during magnetic storms; ground support for radar observations of the ionosphere. To assess the regions most susceptible to geomagnetic hazard, we calculated a map with normalized telluric fields for a uniform magnetic disturbance with a unit amplitude and periods 100–1000 s. This map shows that the geological structure significantly affects the magnitude of the geoelectric fields generated by magnetic disturbances. The database is made publicly available on the anonymous FTP site [ftp://door.gcras.ru/ftp_anonymous/ARCTICA_Rus].